2018
DOI: 10.1029/2017jg004288
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Carbonates Contributes to Coastal Vegetated Ecosystems Keeping Pace With Sea Level Rise in an Arid Region (Arabian Peninsula)

Abstract: Anthropogenic sea level rise (SLR) presents one of the greatest risks to human lives and infrastructures. Coastal vegetated ecosystems, that is, tidal marshes, seagrass meadows, and mangrove forests, elevate the seabed through soil accretion, providing a natural coastline protection against SLR. The soil accretion of these ecosystems has never been assessed in hot desert climate regions, where water runoff is negligible. However, tropical marine ecosystems are areas of intense calcification that may constitute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 78 publications
(99 reference statements)
3
50
1
Order By: Relevance
“…, Saderne et al. ). Carbonic acid formed during microbial respiration and root excretions, and nitric or sulfuric acids formed during nitrogen and sulfur cycling could drive the pH low enough to dissolve carbonate substrates, as observed in seagrass beds of Biscayne Bay, FL (Zieman ).…”
Section: Mechanisms Of Coastal Wetland Peat Collapsementioning
confidence: 99%
See 1 more Smart Citation
“…, Saderne et al. ). Carbonic acid formed during microbial respiration and root excretions, and nitric or sulfuric acids formed during nitrogen and sulfur cycling could drive the pH low enough to dissolve carbonate substrates, as observed in seagrass beds of Biscayne Bay, FL (Zieman ).…”
Section: Mechanisms Of Coastal Wetland Peat Collapsementioning
confidence: 99%
“…The compaction of fine-grained sediments is considered a major contributor to coastal wetland submergence, particularly in deltas, but is typically documented as a deep, gradual process of subsidence (Coleman et al 1998, Meckel et al 2007). Dissolution of mineral matter may be significant in carbonate coastal ecosystems (e.g., Florida Everglades [USA], Yucatan Peninsula, Australia, and the Arabian Peninsula) where carbonates contribute substantially to coastal wetland soil volume (Breithaupt et al 2017, Saderne et al 2018. Carbonic acid formed during microbial respiration and root excretions, and nitric or sulfuric acids formed during nitrogen and sulfur cycling could drive the pH low enough to dissolve carbonate substrates, as observed in seagrass beds of Biscayne Bay, FL (Zieman 1972).…”
Section: Mineral Matter Compaction and Dissolutionmentioning
confidence: 99%
“…The Arabian Gulf, on the other hand, receives water from the Shatt al Arab River in the north, which itself is a result of the confluence of the Tigris and Euphrates Rivers. The sediments of the Red Sea and Arabian Gulf originate mainly from carbonate deposits from seawater and deposited airborne sediment of terrestrial origin, which is reported to comprise up to one-third of Gulf sediments (Sugden 1963, Saderne et al 2018. Dust deposition from frequent dust storms originating in the Sahara and the Arabian Peninsula is believed to be one of the primary sources of nutrients to the Red Sea and the Gulf (Acosta et al 2013, Engelbrecht et al 2017).…”
Section: Ecosystem Descriptionsmentioning
confidence: 99%
“…The Red Sea is oligotrophic, with P and N sea surface concentrations estimated, in its central part, at 0.05-0.1 μmol kg −1 and 0.03-0.2 μmol kg −1 , respectively (Weikert 1987, Wafar et al 2016. Saderne et al (2018) measured surface water concentrations of P and N, in a seagrass (Khor Almasena'a) and mangrove area, from the same study zone, and reported annual mean (±SD) records of 0.8±0.4 μmol P kg −1 and 1.3±0.5 μmol N kg −1 , and 2.3±0.5 μmol P kg −1 and 0.9±0.2 μmol N kg −1 , respectively. The chemical oceanography of the Arabian Gulf has been largely understudied, with only five sampling expeditions since 1965 (although substantial gray literature exists) (Al-Yamani and Naqvi 2019).…”
Section: Ecosystem Descriptionsmentioning
confidence: 99%
See 1 more Smart Citation